A compact triple band circular polarized slotted microstrip patch antenna with low frequency ratio. Issue 12 (12th September 2022) - Bairappaka, Santosh Kumar; Ghosh, Anumoy; Kumar, Jayendra; Bhattacharya, Anagha
Abstract: A pentagon shaped triple band circular polarized (CP) slotted microstrip patch antenna with asymmetric single microstrip feed line is designed. The proposed patch antenna is loaded with a pair of asymmetric slits, a pair of symmetric slots and a triangle shape truncation at the right side of the antenna. The antenna is drafted within the size of 0.43λ × 0.43λ and resonates at 2.17, 3.08, and 3.48 GHz with impedance bandwidth (IBW; IS11 I < −10 dB) 2.14–2.20, 3.06–3.10, and 3.45–3.51 GHz, respectively. The Axial Ratio Bandwidth (ARBW; AR < 3 dB) is obtained as 2.17–2.40, 3.07–3.10, and 3.48–3.54 GHz at the three resonances which almost cover the IBW. An additional feature of the design is that the CP bands are very closely spaced with frequency ratio of 1.36 between first and second CP resonances and 1.13 between second and third CP resonances. The obtained gain at three resonances is 3.9, 3.79, and 4.81, respectively. The CP radiation patterns are found to be stable with good right hand CP (RHCP) to left hand CP (LHCP) isolation at the boresight direction. This antenna is suitable for S‐band applications. The advantage of the proposed design has been highlighted with respect to multiband CP, CP frequency ratio, compactness and RHCP to LHCP isolation. A prototype of the proposed design is fabricated and the measured results are in accord with the simulated results.